The Reasons for the Emigration of Croats to South America Between 1880–1914 and Their Impact in the Political Context - Zanki, Angelika (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
The paper describes Croatian emigration to South America during the first wave of emigration, which took place between 1880–1914. It does that in a political context, considering social, cultural, economic and historical aspects. The starting point for the considerations is the conviction that Croats were motivated to leave the homeland due to the policies of the authorities governing the countries to which Croatia belonged over the years. It analyses the situation of Croats brought about by the policy of the Austro-Hungarian monarchy. It also describes how South American countries encouraged Croats to leave their homeland, as well as how Croats created foundations for the political community in new places of living.